Breaking the Cycle of Trauma – Koori Parenting, What Works for Us - Gee, Graham; Lesniowska, Raelene; Santhanam-Martin, Radhika; Chamberlain, Catherine (First Peoples Child & Family Review, 2020)
Objective: To develop an understanding of parenting strategies used by Aboriginal Australian parents impacted by colonisation and other forms of adversity to break cycles of trauma within families.Design: “Yarning circles” involving qualitative interviews with six Aboriginal parents were conducted. Parents who identified as having experienced childhood histories of trauma and historical loss were asked about parenting strategies that helped them to break cycles of intergenerational trauma. Interviews were transcribed and independently coded by Aboriginal and non-Aboriginal psychologists who worked for an Aboriginal Community Controlled Health Organisation.Results: Parents identified over 100 strategies associated with parenting and breaking cycles of trauma. Some strategies aligned well with research on the protective effects of safe, stable, nurturing relationships. Other strategies focused upon domains of culture, community, and history, and addressed issues such as family violence, colonisation, and the intergenerational links between trauma and parenting. The strategies were collated into a community resource that could be used by other Aboriginal parents.Conclusion: Parental histories of colonisation and interpersonal and intergenerational trauma can have a significant impact on kinship networks and community environments that Aboriginal parenting practices are embedded within. Parents who identified with having managed to break cycles of trauma reported using a wide range of successful parenting strategies. These strategies serve a diversity of functions, such as parenting approaches that aim to directly influence children’s behaviour and foster wellbeing, manage family and community conflict, and manage parental histories of trauma and trauma responses in ways that mitigate the impact on their children.